2009
DOI: 10.1371/journal.pone.0004409
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Ascorbic Acid Is Associated with the Inhibition of Genes Necessary to Cell Cycle Progression

Abstract: BackgroundAscorbic acid (AA), or Vitamin C, is most well known as a nutritional supplement with antioxidant properties. Recently, we demonstrated that high concentrations of AA act on PMP22 gene expression and partially correct the Charcot-Marie-Tooth disease phenotype in a mouse model. This is due to the capacity of AA, but not other antioxidants, to down-modulate cAMP intracellular concentration by a competitive inhibition of the adenylate cyclase enzymatic activity. Because of the critical role of cAMP in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 24 publications
4
48
1
1
Order By: Relevance
“…Microarray data indicate that primary normal human fibroblasts downregulated 31 genes in response to low-end pharmacologic ascorbate treatment (0.3-0.8 mM) with many of the downregulated genes encoding for either tRNA synthetases or translation initiation factors (3). As suggested by the decreased transcription of these genes, treatment of these cells and several human cancer cell lines with pharmacologic ascorbate concentrations resulted in decreased proliferation.…”
Section: Effects On Cell Cyclementioning
confidence: 99%
“…Microarray data indicate that primary normal human fibroblasts downregulated 31 genes in response to low-end pharmacologic ascorbate treatment (0.3-0.8 mM) with many of the downregulated genes encoding for either tRNA synthetases or translation initiation factors (3). As suggested by the decreased transcription of these genes, treatment of these cells and several human cancer cell lines with pharmacologic ascorbate concentrations resulted in decreased proliferation.…”
Section: Effects On Cell Cyclementioning
confidence: 99%
“…Doses of free AA were selected as reported in (1,3,4), and PAL dose was selected based on our preliminary results. Our initial studies with mice injected with 4 g/kg of free AA showed signs of toxicity (data not shown); hence, 1 g/kg dose was selected for subsequent studies.…”
Section: Effect Of Various Formulations On Tumor Growth In Vivomentioning
confidence: 99%
“…This present study addresses the question of whether PAL can produce anticancer activity equal to or greater than the activity of AA therapy, which has been reported to decrease tumor growth rates by about 40% in numerous rodent models (1,3,4). Although PAL are being used to deliver ascorbate, the effects of PAL cannot be expected to be identical to those of injected free AA due to differences in delivery dynamics and biochemical behavior.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Vitamin C is a hydrophilic substance (Akturk et al, 2006;Harapanhalli et al, 1996) that acts as a nutritional supplement and is considered to be very essential in preventing scurvy (Belin et al, 2009). It is known to be an outstanding chain-breaking antioxidant as well as a very good free radical scavenger (Premila, 2005).…”
Section: Introductionmentioning
confidence: 99%